Compound Open Depressed Displaced Frontal Bone and Supraorbital Rim Fracture and Its Associated Injury: A Case Report - Ingrid A Widjaya; Bilzardy F Zulkifli; Muhammad Z Arifin (Universitas Kristen Maranatha, 2019)
Compound open depressed displaced frontal bone and supraorbital rim fracture was an uncommon variant of skull fractures and present a management challenge due to their anatomy and potential associated injuries, including intracerebral hematoma, extraocular muscle injury, and traumatic optic neuropathy. We presented a case of 22 years old male with multiple trauma including moderate head injury presented to our emergency unit with a decrease of consciousness and seizures. The initial GCS was E3M6V4 (13/15). Head CT Scan demonstrated a displaced depressed fracture at left frontotemporal with adjacent intracerebral hemorrhage and cerebral prolapse. The patient underwent an emergency surgery. The fragmented bones were removed, we left the prolapse untouched, followed by duraplasty using a pericranial flap, and we fixed the fragmented supraorbital rim. Within 24 hours follow up, the patient already gains a full consciousness (GCS 15/15). The patient discharged after 3 days hospitalization with stable neurological condition. We concluded proper emergency surgery, removal of bone fragments and fixation on the superior orbital rim contributed to an optimal outcome. Keywords: open depressed fractures, supraorbital rim, frontal bone